INTELLIREHAB: MALAYSIA-UK ACADEMICIANS AND INDUSTRY COLLABORATION TO ASSIST PATIENTS WITH NERVE DISORDERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 13 June 2016 – For the first time, academicians and the industry in Malaysia and the United Kingdom has collaborated to produce a physiotherapy rehabilitation equipment known as 'IntelliRehab' at a cost of approximately RM7 million, supported through the Innovate UK NewtonUngku Omar collaboration grant.